The Educational Aspects of the Story of the Prophet Muses & the Wiseman - Said Rashed Al swafi (Sultan Qaboos University, 2011)
This research studies the story (the prophet Muses with the Wiseman) trying to get as much as it can information relating to educational and ethical aspects. That why it is titled (the Educational Aspects of the Story of the Prophet Muses & the Wiseman). The Holy Quran is way of life, a methodology of education and a source of goals and objectives. It takes great care of human beings to led him to the pest life. To achieve this goal, the Qur'an follows multiple methods and different ways. Among those unique methods is telling stories. However, when the Quran tells story, it doesn't want it to be like a night-story. The Quran, in fact, targets to benefit people throughout the story. A very good example for that is the story (the prophet Muses with the Wiseman). That story is like a real journey for seeking knowledge witch contents many valuable benefits of educational and ethical methods.